Meeting the Needs of Gifted and Talented Students using Differentiated Instruction in Enhancing Chemistry Understanding - Kanapathy, Suganty (International Journal of Academic Research in Progressive Education and Development, 2023)
Differentiated instruction is the practice of tailoring instruction to meet the different needs of students. Differentiated instruction basically help to fulfil ‘no child left behind’ concept. This research aims to explore the use of differentiated instruction approaches in learning chemistry. The respondents of this research comprised of 132 respondents who were chemistry learners from science background, taking chemistry subject as their core subject within the programme. Quantitative and qualitative studies were conducted. The quantitative data were analyzed using SPSS 21.0 to identify significant improvement in students learning and understanding using t-test. Qualitative method was employed to obtain students’ perception on differentiated instruction. Atlas.ti software was used to analyze qualitative data. Based on the analysis, a significant improvement was observed in post-test compared with pre-test. Moreover, t-value was found to be significant, with p<0.05 and this indicates a significant improvement in students learning and understanding of the chapter. Generally, different level of students, namely struggling group, medium group and advance group students gives a positive feedback on differentiated instruction. This paper may help to bring about changes to improve chemistry teaching and learning processes among educators.